1986
DOI: 10.1007/bf01020572
|View full text |Cite
|
Sign up to set email alerts
|

The haustorium and the chemistry of host recognition in parasitic angiosperms

Abstract: Two parasitic angiosperms,Agalinis purpurea (Scrophulariaceae) andStriga asiatica (Scrophulariaceae), are compared as to the chemical recognition events involved in host selection.Agalinis is a hemiparasite which can mature to seed-set without a host, whereasStriga is a holoparasite and survives for only a very limited time without a host. Both parasites, however, attach to a host through a specialized organ known as the haustorium and regulate the development of this organ through the recognition of chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 25 publications
3
98
0
Order By: Relevance
“…Benzoquinones are produced in plants by biosynthesis on the shikimate acid pathway, by oxidative decarboxylation of phenolic acids, and by the enzymatic degradation of cell wall phenols by peroxidases and laccases (Caldwell and Steelink, 1969). Interestingly, DMBQ was identified from sorghum (Sorghum bicolor) roots only after they were physically abraded or coincubated with Striga cultures (Chang and Lynn, 1986). HPLC analyses showed that coincubation of root washes with Striga results in the generation of DMBQ through peroxidase-mediated oxidation of cell wall components (Lynn and Chang, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzoquinones are produced in plants by biosynthesis on the shikimate acid pathway, by oxidative decarboxylation of phenolic acids, and by the enzymatic degradation of cell wall phenols by peroxidases and laccases (Caldwell and Steelink, 1969). Interestingly, DMBQ was identified from sorghum (Sorghum bicolor) roots only after they were physically abraded or coincubated with Striga cultures (Chang and Lynn, 1986). HPLC analyses showed that coincubation of root washes with Striga results in the generation of DMBQ through peroxidase-mediated oxidation of cell wall components (Lynn and Chang, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These were isolated from a fractionation of gum tragacanth, a commercially available, water-soluble mixture of dried Astragalus sap (Steffens et al, 1982). The first and only HIF isolated to date from host roots is 2,6-dimethoxy-p-benzoquinone (DMBQ) (Chang and Lynn, 1986). Benzoquinones are produced in plants by biosynthesis on the shikimate acid pathway, by oxidative decarboxylation of phenolic acids, and by the enzymatic degradation of cell wall phenols by peroxidases and laccases (Caldwell and Steelink, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…These include phenolic acids, flavonoids, and quinones (Estabrook and Yoder, 1998;Kim et al, 1998;Albrecht et al, 1999). The only HIF that has been identified directly so far from plant roots is 2,6-dimethoxy-pbenzoquinone (DMBQ; Chang and Lynn, 1986). The precise mechanisms by which these compounds are released and then trigger haustorium development are not well understood; however, some genes have been identified that may be involved in these processes.…”
mentioning
confidence: 99%
“…Upon germination, the growing seedling generates H 2 O 2 to oxidize host cell wall phenols and release haustorial-inducing p-benzoquinones. 10 These xenognostic signals diffuse back to the parasite and initiate development of the haustorium. (C) Haustorium development.…”
Section: "Tell Me What You Eat and I Will Tell You Who You Are"mentioning
confidence: 99%